Peran Majelis Arbiter dalam Menilai Sengketa Konstruksi: Pendekatan Teknis dan Hukum dalam Arbitrase - Ira Andamara Eddymurthy (Badan Arbitrase Nasional Indonesia, 2026)
Construction disputes differ substantially from ordinary commercial disputes because they involve complex technical dimensions, multiple parties in layered contractual relationships, and heavy reliance on technical and administrative documentation generated during project execution. In Indonesian construction arbitration practice, the arbitral tribunal must not only interpret the contract but also assess the technical facts which require an understanding of construction methods, project management, and relevant engineering standards. This article examines the characteristics of construction disputes, the types of claims most commonly raised, appropriate evidentiary approaches, the role of expert witnesses, site inspections, document discovery mechanisms, and the tribunal’s active role in ensuring that both technical and legal facts are objectively established. A hybrid approach combining contract law and technical analysis is a key prerequisite for tribunals to render arbitral awards that are fair, fact-based, and effectively enforceable in construction practice.